IMPROVE EMPLOYEE PERFORMANCE THROUGH ORGANIZATIONAL CULTURE AND EMPLOYEE COMMITMENTS - Ariawaty, R. Rina Novianty (Jurnal Aplikasi Manajemen, 2020)
Employees are an important factor for increasing productivity to support the organization's progress. Each organization has characteristics that distinguish one organization from another organization, and these characteristics are called organizational culture. An organization that has an influential culture will produce an excellent performance in the long run. In addition to culture, commitment from employees is one of the benchmarks for the success of an organization's performance. This study aims to determine how Employee Performance, Employee Commitment, and Organizational Culture in the Bandung City Investment and One-Stop Integrated Services Office, as well as how Organizational Culture and Employee Commitments Influence Employee Performance in the Investment Office and One-Stop Integrated Services in Bandung City. This research uses quantitative methods with descriptive and varied approaches. This study uses a sample of the population of employees in the Office of Investment and Integrated Services One Door Bandung. The sample used was 116 respondents and data collection using direct survey methods and questionnaire instruments. The data obtained were analyzed using the Partial Least Square analysis technique. The results showed the relationship between organizational culture and significant effect on performance and the relationship of employee commitment and significant effect on employee performance